Multi-Objective Optimization Design of Standard Industrial Motor - Tran, Tuan V; Dang, Chi D (Old Journal, 2020)
This paper presents a method to optimally design electrical machines. Unlike the traditional design method “tries-and-errors iterative process”, the optimal design approach consists of combining optimization algorithms and multi-physics models to reach the optimum design. A case study of designing a standard industrial motor of 6 HP with multi-objectives and constraints is chosen in order to test this optimization methodology. The Pareto solution results of two conflicting objectives between the efficiency and the active mass of this machine are reached to help designers and customers selecting the best compromised design of motor of 6 HP in terms of cost and consuming energy.